Rozwój dziewcząt afrykańskich w okresie pokwitania w zróżnicowanych wârunkach środowiskowych - Kolasa, Ewa (Polskie Towarzystwo Antropologiczne, 1988)
GROWTH OF AFRICAN' GIRLS DURING ADOLESCENCE IN VARIED ENVIRONMENTAL ONDIHONS.'Using the data found in literature'and collected by the author, the growth of girls representing irious environments and social strata from Zaire, Rwanda, Uganda, Nigeria, Gambia/ and Somalia is discussed, king into account body height and weight and the age at menarche. An attempt is made to assess the secular end in thé development'of Zairean and Nigerian girls.
GROWTH OF AFRICAN' GIRLS DURING ADOLESCENCE IN VARIED ENVIRONMENTAL ONDIHONS